2019
DOI: 10.1097/rti.0000000000000465
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Perinodular Emphysema in High-risk Patients Offers No Benefit in Lung Nodule Risk-Stratification of Malignancy Potential

Abstract: Purpose: Pulmonary nodules, found either incidentally or on lung cancer screening, are common. Evaluating the benign or malignant nature of these nodules is costly in terms of patient risk and expense. The presence of both global and regional emphysema has been linked to increased lung cancer risk. We sought to determine whether the measurement of emphysema directly adjacent to a lung nodule could inform the likelihood of a nodule being malignant. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…By conducting univariate analysis of patients' general information (age, course of disease, BMI, nodule diameter, and gender), smoking status (smoking history and number of cigarettes smoked per year), medical history (family history of lung cancer, history of extrapulmonary malignant tumor, and history of autoimmune diseases), basic complications (hypertension and diabetes), and laboratory examinations (CEA, NSE, CYFRA21-1, SCC-Ag, and CA125), it was concluded that age, course of disease, nodule diameter, CEA positive, CYFRA21-1 positive, and CA125 positive were significantly different between the two groups ( P < 0.05); and the logistic regression results showed that high age, increased nodule diameter, and CYFRA21-1 positive were the independent risk factors for developing lung adenocarcinoma from SPN ( P < 0.05). Related studies [ 22 , 23 ] confirmed that the risk of malignancy will be increased in SPN patients at an advanced age, and the prediction model by William H. Amundson [ 24 ] et al showed that more than 50% of patients with pulmonary nodules over the age of 60 years were confirmed as malignant lesions, whereas only 3% of patients under the age of 40 years had malignancy. Moreover, many references mentioned that smoking is the most common risk factor for lung cancer, and its exposure intensity and duration are proportional to the risk of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…By conducting univariate analysis of patients' general information (age, course of disease, BMI, nodule diameter, and gender), smoking status (smoking history and number of cigarettes smoked per year), medical history (family history of lung cancer, history of extrapulmonary malignant tumor, and history of autoimmune diseases), basic complications (hypertension and diabetes), and laboratory examinations (CEA, NSE, CYFRA21-1, SCC-Ag, and CA125), it was concluded that age, course of disease, nodule diameter, CEA positive, CYFRA21-1 positive, and CA125 positive were significantly different between the two groups ( P < 0.05); and the logistic regression results showed that high age, increased nodule diameter, and CYFRA21-1 positive were the independent risk factors for developing lung adenocarcinoma from SPN ( P < 0.05). Related studies [ 22 , 23 ] confirmed that the risk of malignancy will be increased in SPN patients at an advanced age, and the prediction model by William H. Amundson [ 24 ] et al showed that more than 50% of patients with pulmonary nodules over the age of 60 years were confirmed as malignant lesions, whereas only 3% of patients under the age of 40 years had malignancy. Moreover, many references mentioned that smoking is the most common risk factor for lung cancer, and its exposure intensity and duration are proportional to the risk of lesions.…”
Section: Discussionmentioning
confidence: 99%